How much does spoken language affect spelling among primary school pupils? Quantitative research on spelling over the period of 1950–2021 - Čičirkaitė, Ramune (Taikomoji kalbotyra, 2023)
Quantitative analysis of spelling among primary school pupils revealed that the spelling of primary school pupils was highly variable, but not chaotic. Despite deviations from norms, primary school pupils, probably based on the internal consistency of spelling, attempted to establish uniformity in their spelling by writing the same sounds or their combinations with the same orthographic codes. The theoretical consistency, grounded in spelling conventions, was statistically significantly higher in the essays of older primary school pupils compared to their younger counterparts, suggesting a potential influence of superior cognitive abilities in older children.The analysis confirmed the assumption that spoken language is a primary factor contributing to spelling variations in our primary school children. Its impact is particularly prominent in grades 1–2. Although teachers use corrections to maintain spelling consistency, only one-seventh of primary school children’s spelling remains unaffected by it.It was determined that spoken language alone accounted for spelling variations in one-fifth of primary school pupils. Additionally, one-fifth exhibited a stronger influence from causes other than spoken language, indicating a diverse range of factors affecting spelling. A small portion of primary school children had spelling influenced exclusively by factors unrelated to spoken language.Contrary to common assertions in the public sphere, the data of this research did not support claims of a decline in literacy among schoolchildren. No statistically significant difference was observed in the frequency of words failing to meet norms when comparing the spelling of primary school pupils from the Soviet era to the current period. Current primary school children do not exhibit a significantly higher tendency to write based on spoken language than their counterparts in the Soviet era.
Keywords: literacy; writing; spelling; spoken language; sociolinguistics